Pengaruh Struktur Kepemilikan Terhadap Nilai Perusahaan Dengan Kebijakan Hutang Sebagai Variabel Intervening (Studi Pada Perusahaan Sektor Perdagangan, Jasa dan Investasi yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2009-2015) - Septiani Pratiwi; Gerry Ganika (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This research determines to prove that ownership structure influence to firm value, by using the debt decisions as a intervening variable. Sample use in this research are trading, services and investment company which listed on Indonesia Stock Exchange during 2009-2015, and purposive sampling method are use to determine he quantity of sample within consist of 175 sample. Analysis method that use was path analysis, sobel test and t-test. Path analysis and hyphothesis test shows that : 1) ownership structure has a negative and significant influence to the firm value, 2) ownership structure has a positive and non-significant influence to the debt decisions, 3) debt decisions has a negative and significant influence to the firm value, and 4) from the path analysis shows that debt decisions as intervening variables can’t mediate ownership structure to the firm value.